Pengaruh Kepemimpin terhadap Kinerja Guru di Madrasah Tsanawiyah Sirojul Ulum, Sukabumi - Yuni Pambreni; Suci Ayu Sudari; Siti Listiana (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research aims to test the effect of leadership on teacher performance at Madrasah Tsanawiyah Sirojul Ulum, Sukabumi Regency. The research design used in this study is descriptive and associative methods. Descriptive method is research conducted to determine the value of independent variables, either one or more (independent) variables without making comparisons, or connecting with other variables. While the associative method is research that aims to determine the influence or also the relationship between two or more variables. This associative method is used to determine the effect of the two variables. Unit analysis in this research is individual i.e. teacher in Madrasah Tsanawiyah Sirojul Ulum Sukabumi Regency, population and sample is all teacher in Madrasah Tsanawiyah Sirojul Ulum 30 teachers in total. The result indicated that leadership (X) ‘s influence on teacher performance (Y) is at 93% and the rest 7% is influenced by other variables that are not in this research